Are Guanxi-Type Supervisor–Subordinate Relationships Culture-General? An Eight-Nation Test of Measurement Invariance. (July 2014) - Smith, Peter B.; Wasti, S. Arzu; Grigoryan, Lusine; Achoui, Mustafa; Bedford, Olwen; Budhwar, Pawan; Lebedeva, Nadya; Leong, Chan Hoong; Torres, Claudio
Three dimensions of subordinate–supervisor relations (affective attachment, deference to supervisor, and personal-life inclusion) that had been found by Y. Chen, Friedman, Yu, Fang, and Lu to be characteristic of a guanxi relationship between subordinates and their supervisors in China were surveyed in Taiwan, Singapore, and six non-Chinese cultural contexts. The Affective Attachment and Deference subscales demonstrated full metric invariance whereas the Personal-Life Inclusion subscale was found to have partial metric invariance across all eight samples. Structural equation modeling revealed that the affective attachment dimension had a cross-nationally invariant positive relationship to affective organizational commitment and a negative relationship to turnover intention. The deference to the supervisor dimension had invariant positive relationships with both affective and normative organizational commitment. The personal-life inclusion dimension was unrelated to all outcomes. These results indicate the relevance of aspects of guanxi to superior–subordinate relations in non-Chinese cultures. Studies of indigenous concepts can contribute to a broader understanding of organizational behavior.